Caring Connections: Unveiling Supportive Needs for Enhanced Quality of Life in Young Women with Breast Cancer - Parvaneh Aghajari; Mina Hosseinzadeh; Farnaz Rahmani; Faranak Jabbarzadeh; Sheila Hurst (Journal of Caring Sciences)
Introduction: Providing supportive care to cancer patients can improve their quality of life (QOL). The present study aimed to determine the met and unmet supportive care needs of young women with breast cancer and their relation with their QOL. Methods: In this cross-sectional correlational study, 275 women under 50 years old with breast cancer under chemotherapy who were selected by a convenience sampling method in 2020-2021 at Tabriz, Iran, participated. Data were collected by questionnaires and were analyzed using descriptive statistics and inferential statistics by SPSS software version 13. Results: The mean (SD) score of supportive care needs was 87.25(23.27). The most common unmet needs among patients were psychological needs. The mean (SD) scores of QOL in the functional and symptom domains were 36.21(4.23) and 41.91(6.57), respectively. Total supportive care needs had a significant and negative relationship with the functional areas of QOL in both the EORTC QLQ-C30.V.3 (r=0.15, P=0.007) and EORTC QLQ-BR23 (r=-0.46, P<0.001) and a significant positive relationship with the symptom domain in both the EORTC QLQ-C30.V.3 (r=0.32, P<0.001) and EORTC QLQ-BR23 (r=0.11, P=0.03). Conclusion: Patients with breast cancer require a variety of supportive care during treatment. Supportive care programs, particularly during chemotherapy or hormone therapy, are essential for reducing patients’ unmet needs and improving their QOL.